Red seas under red skies ebook - Lynch, Scott (Gentleman Bastard, 2007)
In the second book of the suspense-filled Gentleman Bastard Sequence, hailed by George R. R. Martin as “fresh, original, and engrossing,” Locke Lamora faces a caper so death-defying that nothing short of a miracle will pull it off. For some, only a prize worth dying for makes life worth living. . . .   After a brutal battle with the underworld, Locke and his sidekick, Jean, fled to the exotic shores of Tal Verrar to nurse their wounds. But they are soon back to what they do best—stealing from the rich and pocketing the proceeds. Now, however, they have targeted the grandest prize of all: the Sinspire, the world’s most exclusive, most heavily guarded gambling house. But there is one cardinal rule: it is death to cheat at any game.   Brazenly undeterred, Locke and Jean have orchestrated an elaborate plan to lie, trick, and swindle their way straight to the Sinspire’s teeming vault. But someone knows the duo’s secret—and has every intention of making them pay for their sins. . . .   Don’t miss any of Scott Lynch’s epic fantasy Gentleman Bastard Sequence: THE LIES OF LOCKE LAMORA • RED SEAS UNDER RED SKIES • THE REPUBLIC OF THIEVES